AS RELAÇÕES DA LIDERANÇA AUTÊNTICA E DO DESENGAJAMENTO MORAL À SEGURANÇA DA INFORMAÇÃO ORGANIZACIONAL - SILVA, CAMILA BERNARDO DA (2019)
The technology has been transforming management into organizations.The development of information technology has played an important role in the administration, as an important tool of management and control for the companies, contributing to the competitive scenario. Although, all the gains offered by information systems to companies and their managers, the violation of information systems, can have negative effects on the results of these organizations.This research have aims to investigate the relationship between authentic leadership and moral disengagement in relation of violating information security policies. Based on a quantitative research approach with a single cross-section, the sample consists of 201 questionnaries answered and validated. For the hypothesis tests of the study, the analysis of structural equations was performed, to the proposed research model. The results presented confirm that Moral Disengagement influences positively the Intention of Violation of Information Security Policy, the Authentic Leadership as antecedent factor of Intention of Violation of Information Security Policy had no effect.